High concentration of plasma methoxytyramine: dopamine-producing tumour or Parkinson's disease therapy?. (July 2019) - Chtioui, Haithem; Sadowski, Samira M; Winzeler, Bettina; Tschopp, Oliver; Grouzmann, Eric; Abid, Karim
Background: Levodopa (L-DOPA) provided to patients with Parkinson's disease causes an increase in dopamine and methoxytyramine blood concentration which may lead to erroneous diagnosis of dopamine-producing tumours based on a plasma fractionated metanephrines and methoxytyramine assay. Considering that oral L-DOPA is mainly transformed in the gut wall into dopamine and methoxytyramine, we hypothesize that patients treated with L-DOPA produce predominantly sulphated methoxytyramine, whereas dopamine-producing tumours, devoid of sulfotransferase, will secrete free methoxytyramine. These metabolic differences may allow for discrimination between the two groups of patients through methoxytyramine plasma concentration. Methods: We retrospectively investigated a cohort of 16 patients with a dopamine-secreting pheochromocytoma or paraganglioma and 22 patients treated for Parkinson's disease to see whether the metabolic ratio of free and sulphated methoxytyramine differs. Results: Receiver operating characteristic curve analysis indicates an absolute separation between the two groups when using a cut-off of free/total methoxytyramine (sum of free and sulphated methoxytyramine) ratio of 0.0059, corresponding to a free methoxytyramine fraction of 0.59% ( P  < 0.0001, AUC 1.0 indicating 100% sensitivity and specificity). Conclusion: Dopamine secreted by tumours and exogenous dopamine (from Parkinson's disease treatment) follow different metabolic pathways. We observed that free/total methoxytyramine ratio may be a useful tool in distinguishing between patients with a dopamine-secreting tumour from patients treated with L-DOPA when clinical information is incomplete or lacking.